The dispersal and social exclusion of asylum seekers : between lininality and belonging / Patricia Hynes. - Hynes, Patricia (Policy Press, 2011)
Establishing asylum seekers in the UK as a socially excluded group, this book provides readers with an understanding of how they experience the dispersal system and gives an insight into how this impacts on their lives.